1997
DOI: 10.1046/j.1471-4159.1997.68052111.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Cerebral Acyl‐CoA Concentrations Following Ischemia‐Reperfusion in Awake Gerbils

Abstract: Transient global cerebral ischemia affects phospholipid metabolism and features a considerable increase in unesterified fatty acids. Reincorporation of free fatty acids into membrane phospholipids during reperfusion following transient ischemia depends on conversion of fatty acids to acyl-CoAs via acyl-C0A synthetases and incorporation of the acyl group into lysophospholipids.To study the effect of ischemia-reperfusion on brain fatty acid and acyl-CoA pools, the common carotid arteries were tied for 5 mm in aw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
38
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 54 publications
2
38
0
Order By: Relevance
“…The sample was loaded onto the washed cartridge and the polar components were eluted with 5 ml of 25 mM KH2PO4 buffer (pH 4.9). The acyl-CoA fraction was eluted using a 75:25 (vol/vol) solution of 0.15 ml of 2-propanol and 1 mM acetic acid (39). A portion of this eluent was directly used for separation of the acyl-CoA species on a Phenomenex Luna C-18 (2) column (4.6 ϫ 250 mm), and the individual acyl-CoA values were quantified by UV absorbance measurements.…”
Section: Animalsmentioning
confidence: 99%
“…The sample was loaded onto the washed cartridge and the polar components were eluted with 5 ml of 25 mM KH2PO4 buffer (pH 4.9). The acyl-CoA fraction was eluted using a 75:25 (vol/vol) solution of 0.15 ml of 2-propanol and 1 mM acetic acid (39). A portion of this eluent was directly used for separation of the acyl-CoA species on a Phenomenex Luna C-18 (2) column (4.6 ϫ 250 mm), and the individual acyl-CoA values were quantified by UV absorbance measurements.…”
Section: Animalsmentioning
confidence: 99%
“…Numerous methods have been developed to measure individual long-chain acyl-CoA mass in mammalian tissues (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). However, most of the reported methods demonstrate low recovery of the acyl-CoA extraction, with recovery ranging from 10% to 45% (7,12,16,21).…”
mentioning
confidence: 99%
“…In this paper, we describe modifications of an existing method (17,19) using solid-phase extraction and subsequent HPLC separation of long-chain acyl-CoAs for use with small amounts of tissue ( Ͼ 25 mg). Our modifications increase the recovery of the extraction procedure in excess of 80%, with high reproducibility and significantly improved separation of the most common polyunsaturated and saturated acyl-CoAs.…”
mentioning
confidence: 99%
“…Protective action of pantothenate derivatives have been reported in situations accompanied by oxidative stress, for example, in experimental ischemia-reperfusion of myocardium. It has been shown that antioxidative and membrane-protective effects of the pantothenate derivatives are accompanied by an activation of biosynthesis CoA system and increasing of intracellular level of a free CoA [108,109]. Presumably, the mechanism of cell protection is CoAdependent or realized through CoA-(acyl-CoA)-dependent biochemical reactions, including rise of intracellular glutathione level and maintenance of its redox status.…”
Section: Role Of Coa In Mechanisms Of Neuroprotection In Brain Ischemmentioning
confidence: 99%
“…This function maintains constant flow of oxidative substrates and their effective using for ATP formation in the citric acid cycle [109,110,111].…”
Section: Role Of Coa In Mechanisms Of Neuroprotection In Brain Ischemmentioning
confidence: 99%